PENCIPTAAN BUKU ILUSTRASI TARI TOPENG PANJI MALANGAN UNTUK MEMPOPULERKAN BUDAYA TRADISIONAL KOTA MALANG KEPADA REMAJA - Ghozali, Moh Afrizal; Fianto, Achmad Yanu Alif; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2015)
Abstract:The aim of this study is to provide education about the traditional culture of the city of Malang to adolescents. Introducing traditional art flag Malang Mask Dance in the wider community, especially teenagers. The study was conducted using qualitative research method is by conducting interviews, observation, documentation, and literature to obtain the data used to support the manufacture of the design concept of branding. Data were analyzed using several stages, namely data reduction, data presentation, and conclusion. From the data analysis found some keywords that refer to creative planning to reach the intended target audience. After analyzing the data, found a concept or keyword creation illustrated book is